On the Influencing Factors and the Continuous-Improving Mechanism of China’s Energy Efficiency - Jing, Yong Ping; Wen, Dan Dan (Applied Mechanics and Materials, 2014)
With the continuous development of economic globalization and the overall deepening of China's reform and opening up, energy efficiency has increasingly become a major strategic issue related to national social-economic development, energy security and environmental protection. At present, the general trend of energy efficiency in China is continuously improving, but the development among regions is seriously uneven. There is still a big difference compared with the current and the international advanced level. Therefore, establishing the policy support system and the long-term development mechanism helping to continuously improve energy efficiency will undoubtedly be a strategic topic both for present and future.